Monetary Policy and Swedish Unemployment Fluctuations - Annika Alexius; Bertil Holmlund (Kiel Institute for the World Economy (IfW), 2007)
A widely spread belief among economists is that monetary policy has relatively short-lived effects on real variables such as unemployment. Previous studies indicate that monetary policy affects the output gap only at business cycle frequencies, but the effects on unemployment may well be more persistent in countries with highly regulated labor markets. We study the Swedish experience of unemployment and monetary policy. Using a structural VAR we find that around 30 percent of the fluctuations in unemployment are caused by shocks to monetary policy. The effects are also quite persistent. In the preferred model, almost 30 percent of the maximum effect of a shock still remains after ten years.
Keywords: E24; J60; 330; Unemployment; Monetary policy; structural VARs; Geldpolitik; Schock; Arbeitslosigkeit; Hysteresis; Schätzung; Schweden